2D Game “Omar’s Adventure” design using the Finite State Machine Method - Rashad Fathin Kurniawan; Fresy Nugroho; Puspa Miladin Nuraida Safitri Abdul Basid; Firma Sahrul Bahtiar; Raihan Nafal Zuhdi Simamora; Geovanni Azam Janitra; Juniardi Nur Fadilah (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2022)
A video game is a game that has rules in it that must be obeyed when the game takes place so that the video game ends either in a win or a loss, played with a device / console. Video games themselves consist of various kinds, one of which is 2D video games. A 2D game is a game that only has 2 spaces or 2 axes, namely the X and Y axes. This research was conducted with the aim of incorporating Islamic elements into a video game so that players can recognize and learn Islamic elements through more interesting media. The result of the research is a 2D game called "Omar's Adventure" which was designed using the Unity game engine, and applied the Finite State Machine (FSM) method in making the game. The FSM given in this game will make several NPCs move / react according to the player's movements to add interactivity in playing it. The resulting game contains the adventure of Omar, where he needs to pass the levels or obstacles that prevent him from his goal in the form of the path of goodness